1981
DOI: 10.1149/1.2127349
|View full text |Cite
|
Sign up to set email alerts
|

The Detection of Structural Defects in Indium Phosphide by Electrochemical Etching

Abstract: Two new etching procedures for InP are described; one for damage removal with retention of surface flatness, and the other for high resolution defect delineation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The reduction potential of the reactant and products in Eq. [3] is strongly tied to the nucleophilic attack of X -. It has been found that the dissolution of In +8 from In or I n ( H g ) e l e c t r o d e s in CI-, B r -, I -, or S C Nsolutions is via a ligand bridge intermediate (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction potential of the reactant and products in Eq. [3] is strongly tied to the nucleophilic attack of X -. It has been found that the dissolution of In +8 from In or I n ( H g ) e l e c t r o d e s in CI-, B r -, I -, or S C Nsolutions is via a ligand bridge intermediate (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism, rate, and suppression of n-type III-V semiconductor oxidation plays a critical role in several scientific areas. Chemical oxid'ation of semiconductors is a well-known method of polishing and removing damage from III-V surfaces (1) and electrochemical etching (2)(3)(4) has been used to study crystal defects. The characterization (5)(6)(7)(8) of the GaAs and InP semiconductor/aqueous solution interface and study of its photo-oxidation (9)(10)(11)(12)(13)(14) has led to the design of stable photovoltaic cells for the conversion of optical power into chemical and/or electrical power (15)(16)(17)(18), More recently, the advent of solid-state devices based on III-V materials for use in optical communication and high speed electronic systems has created new interest in the etching and selective etching (19)(20)(21)(22) of the semiconductors.…”
mentioning
confidence: 99%
“…Figure 10 shows a typical SEM micrograph of a hollowedout grappe feature observed on a {110} unetched cleavage face. surface has been proposed by Elliott and Regnault (10).…”
Section: X-ray Topography Of Inclusionsmentioning
confidence: 99%
“…Chemical etching is the simplest method for revealing dislocations and other defects in crystals. A number of papers have been published recently dealing with chemical, electrochemical, and photochemical etching of InP (7)(8)(9)(10)(11), InGaAs (12,13), and InGaAsP grown on <111> B InP (14,15). However, the <100> orientation is widely utilized for LED's, lasers, and other devices, but no chemical etchant that selectively reveals dislocations in <100> InGaAsP layers has yet been reported.…”
mentioning
confidence: 99%